Analisis Pengaruh Inflasi, BI Rate dan Kurs Terhadap Simpanan Masyarakat Melalui Harga Emas dan Indeks Kedalaman Kemiskinan di Kota Medan: Indonesia - Ainur Oktania; Joko Suharianto (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2026)
Changes in macroeconomic variables such as inflation, policy interest rates, and exchange rates can influence people's economic behavior, including decisions to save funds in the banking sector. This study aims to analyze the effect of inflation, the BI Rate, and the exchange rate on community savings in Medan City, both directly and indirectly through gold prices and the Poverty Depth Index. The study uses time series data for the period 2005-2024 obtained from the Central Statistics Agency and Bank Indonesia. The method used is path analysis with the assistance of EViews 10 software. The results show that the exchange rate has a positive and significant effect on gold prices and the Poverty Depth Index, while inflation and the BI Rate have no significant effect. In the community savings model, gold prices, the BI Rate, and the exchange rate have a significant effect on community savings, while inflation and the Poverty Depth Index have no significant effect. In addition, the exchange rate has a significant indirect effect on community savings through gold prices. These findings indicate that the exchange rate plays an important role in influencing gold prices and community savings behavior.